Mathematical study of Kargil War and Indo-China war - Santosh Kumar Rath, Dr. Banitamani Mallik, Colonel (Dr.) Jyotirmaya Satpathy (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Nations want the people to support the war in times of conflict. The loss of innocent lives is an inevitable part of war .The focus of the paper is to mathematically understand and fit in the war of Kargil between India and Pakistan and to understand how the whole war could be understood. This study would help us to understand the war mathematically and to implement the same if there is war like situation between the rising tensions between India and China